A Comparative Study on Compression of Different Image File Formats - Ooi, Poh San (1999)
Advances in imaging technology and computer communications have provided users with a variety of new services that use images, including video conferencing, videophones, multimedia system and High Density television. To fully utilize such a high tech communication system, image compression techniques play an important role in transmission and storage of information. In this project, an image compression format and algorithm has been analyses. A system has been created for user to convert or display image file format. The ScanJet 11C Scanner was used to scan the image. The image was coded into BMP, TIFF files, and GIF decoded and displayed on the screen. Some of the experiment was done twice with two different types of images to ensure that the results were accurate. The Algorithms used to compress and decompress the image ware Run Length Encoding (RLE) algorithm and Lampel-ziv and Welch (LZW) algorithm. One system was developed for users to convert the image file format to enable them to view the size of each image and to display image. From the study, it can be concluded that LZW algorithm is better than RLE algorithm in term of percentage compression. Beside that, the quality of image that can be produced by LZW algorithm and RLE algorithm is almost the same.